Efficient Coding of Excitation Patterns Combined with a Transform Audio Coder - Niemeyer, Oliver; Edler, Bernd (118th AES Convention, 2005)
An efficient encoding of excitation patterns designed for bit rates between 4 and 10 kbit/s is presented. It is based on a two dimensional transform of the excitation patterns in frequency and time direction, followed by a bit plane encoding of the resulting transform coefficients. The bit plane encoding ensures, that all significant coefficients are captured, both for excitation patterns resulting from more tonal and transient like audio signals. In such a way, coded excitation patterns can be used in a scalable noise coder, but also can substitute the scale factors, which usually control the quantisation in subband/transform audio coders. A subband/transform audio coding scheme is presented, which combines these two applications in one system. <p